Syntaxin 3 is haplosufficient for long-term photoreceptor survival in the mouse retina - Perez-Hurtado, Mariajose; Dao, Calvin; Saenz, Amanda E.; Heidelberger, Ruth (Frontiers in Ophthalmology, 2023)
Biallelic loss-of-function mutations in the syntaxin 3 gene have been linked to a severe retinal dystrophy in humans that presents in early childhood. In mouse models, biallelic inactivation of the syntaxin 3 gene in photoreceptors rapidly leads to their death. What is not known is whether a monoallelic syntaxin 3 loss-of-function mutation might cause photoreceptor loss with advancing age. To address this question, we compared the outer nuclear layer of older adult mice (≈ 20 months of age) that were heterozygous for syntaxin 3 with those of similarly-aged control mice. We found that the photoreceptor layer maintains its thickness in mice that are heterozygous for syntaxin 3 relative to controls and that photoreceptor somatic counts are comparable. In addition, dendritic sprouting of the rod bipolar cell dendrites into the outer nuclear layer, which occurs following the loss of functional rod targets, was similar between genotypes. Thus, syntaxin 3 appears to be haplosufficient for photoreceptor survival, even with advancing age.